Employees’ human capital: multiple-case studies of small manufacturing firms - Omar, Siti Sarah; Ariffin, Zailin Zainal; Mahadi, Nomahaza; Ahmad, Zubidah; Ramlan, Rohaizan (American Scientific Publishers, 2018)
The concept of human capital (HC) has received a tremendous emphasis in the Human Resource Management (HRM) literature and in the managerial practice over the last 15 years. While the study of the relationship between employees’ HC and firms’ performance have been conducted to a great degree, yet to what extent HRM functions have implemented activities to encourage HC management is relatively under explored. Therefore this paper seeks to answer these objectives: to identify the dimensions of employees’ HC in small manufacturing firms; and, to identify to what extent HRM practices support the development of HC dimensions of these employees. This is a qualitative study using an in-depth face-to-face interview methodology which has been carried out in five small food manufacturing companies in the Southern Region of Malaysia. The interview transcripts were transcribed and analyzed using thematic analysis. Results show that knowledge, experience and skills were relatively low emphasis by the small business-owners, yet two newly discovered dimensions which are commitment and values are being more prominence. This study concludes that both themes: cognitive and behavioral HC of small manufacturing firms in the Southern Part of Malaysia are not well emphasized and stressed by the small business-owners, thus leading to a disappointing way of performing HRM practices to enhance employees’ HC. This study adds value to HC literature that values and commitments are of important dimensions of HC. Concerning contributions on the managerial practice, this study offers set of recommendations to be applied by the small business-owners.